S45 Functional KCa3.1 K+ channels are required for human fibrocyte migration. (16th November 2010) - Duffy, S M; Cruse, G; Singh, S; Doe, C; Saunders, R; Brightling, C E; Bradding, P
Abstract : Background: Fibrocytes are bone marrow-derived CD34 + collagen I + cells present in peripheral blood that are implicated in the pathogenesis of tissue remodelling and fibrosis in both asthma and pulmonary fibrosis. Ion channels play key roles in cell function, but the ion channel repertoire of human fibrocytes is not known. The aim of this study was to assess whether human fibrocytes express the KCa 3.1 K + channel. Methods: Human fibrocytes were isolated from peripheral blood taken from both normal and asthmatic subjects and maintained in cell culture. Channel expression was examined using RT-PCR, Western blot, and patch clamp electrophysiology. Migration assays were performed using the Transwell system. Results: Fibrocytes expressed both KCa 3.1 mRNA and protein. At baseline unstimulated fibrocytes (n=30 healthy cells from 7 donors, n=17 asthmatic cells from 4 donors) demonstrated heterogeneity of the resting whole cell current, with a small outwardly rectifying current in 91% of cells, a steeply inwardly rectifying current in 30% of cells, and a linear current in 9% of cells. The KCa 3.1 opener 1-EBIO (100 mM) elicited typical KCa 3.1 currents in 46/47 cells tested. Whole cell current at +40 mV increased from 122±25 pA pre-1-EBIO to 795±104 pA post 1-EBIO (p<0.0001). This was accompanied by a negative shift in reversal potential from −29.8±3.0 mV to −61.8±1.6 mV (p<0.0001). 1-EBIO induced a greater current in asthmatic fibrocytes (1-EBIO-dependent current at +40 mV 969±216 pA; n=17 cells) compared to healthy fibrocytes (1-EBIO-induced current 506±94 pA; n=30 cells; p=0.029). KCa 3.1 currents were blocked by the selective KCa 3.1 blocker TRAM-34. The migration of differentiated fibrocytes induced by airway smooth muscle supernatant was inhibited by 71.1±6.9 % by TRAM-34 200 nM (p<0.0001). The CXCL12-dependent migration of fibrocyte progenitors within a freshly isolated PBMC population was reduced by 70.9±7.9% by TRAM-34 (p=0.003). Conclusions: The K + channel KCa 3.1 is expressed in human fibrocytes, and plays a key role in their migration. KCa 3.1 blockers may therefore offer a novel approach to the treatment of airway wall remodelling in asthma, and parenchymal fibrosis in idiopathic pulmonary fibrosis.